ALLOCATION OF BIOMASS IN BAMBOO PLANT IN RESPONSE TO THE MINERAL FERTILIZATION - OLIVEIRA, Dagmar Alves de; BEZERRA NETO, Egídio; NASCIMENTO, Clístenes Willians Araújo do; FERNANDES, Michelangelo Bezerra; SILVA, Tereza Cristina da; OLIVEIRA, Rodrigo Alves de (Scientia Agraria, 2008)
The present study aims to evaluate the influence of mineral fertilization on the allocation of biomass in the roots, culm and leaves of bamboo plants cultivated in green house. The soil is classified as Quartzipsamment, and it was fertilized with the doses equivalent to 0, 20, 40, 80, and 120 kg ha-1 of nitrogen and 0, 10, 40, 80, and 100 kg ha-1 of phosphorus and potassium. The experimental design was randomized blocks with four replications. Bamboo plants were grown for 120 days in green house. After this period the plants were harvested and the total biomass was determined as well the biomass allocation in leaves, culm and roots. The highest total dry weight biomass was achieved by the dose of 120, 10 e 100 kg ha-1 of NPK. The highest biomass production in leaves, was obtained with the dose equivalent to 80, 10 and 100 kg ha-1 NPK. The highest culm biomass biomass production was with the doses equivalent to 120, 40 and 100 kg ha-1 NPK. And the highest production in the root was achieved respectively by the doses of 80, 10 and 100 kg ha-1 of NPK. The fertilization whit N and K provided increase in the production of the total biomass of the bamboo plants.